Antibacterial Activity of Dayak Onion Bulbs (Eleutherine palmifolia (L) Merr) Ethanol Fraction against Pseudomonas fluorescens and Its Secondary Metabolite Analysis - Immaria Fransira; Annisa Fitri Anggreini; Uun Yanuhar; Maftuch Maftuch (Research Journal of Life Science, 2019)
Pseudomonas fluorescens is a gram-negative pathogenic bacteria which is one of the problems in fish farming that can causes death in fish. The alternative to overcome this bacterial attack is by using of natural material such as dayak onion bulbs (Eleutherine palmifolia (L) Merr), which are known to have secondary metabolites. The purpose of this research was to determine the antibacterial activity against P. flourescens that contained in the dayak onion bulbs (E. palmifolia (L) Merr) ethanol fraction and the content of antibacterial compounds from the best dayak onion bulbs (E. palmifolia (L) Merr) ethanol fraction. The method used in this research was antibacterial test with MIC (Minimum Inhibitory Concentration) followed by disc test and FTIR (Fourier Transform Infrared Spectroscopy) to analysis secondary metabolite. Fractionation was conducted using Chloroform: Methanol (9:1 v/v). MIC test result showed that 100 ppm was the minimum concentration that can inhibit the growth of P. fluorescens. Disc test reported that fraction 4 was the best fraction, with the dominant compounds that contained in the bulbs was phenolic compound based on FTIR test. So, the fraction of dayak onion bulbs (E. palmifolia (L) Merr) can be used as potential leads to discover new drugs.